2010
DOI: 10.1021/ma1007418
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hierarchical Self-Assembly of Rod−Rod Block Copolymers via Click Chemistry between Mesogen-Jacketed Liquid Crystalline Polymers and Helical Polypeptides

Abstract: A series of novel rod-rod diblock copolymers containing poly{2,5-bis[(4-methoxyphenyl)-oxycarbonyl]styrene} (PMPCS) and poly(γ-benzyl-L-glutamate) (PBLG) were synthesized by click chemistry from alkyne-and azide-functionalized homopolymers. The R-alkyne PMPCS homopolymers were synthesized by copper-mediated atom transfer radical polymerization with a bromine-containing R-alkyne bifunctional initiator, and R-azido PBLG homopolymers were synthesized by ring-opening polymerization of γ-benzyl-L-glutamate N-carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 55 publications
4
42
0
Order By: Relevance
“…Both PMPCS and PBLG rods were packed in an interdigitated way in their own domains (Scheme X, d and e). These results obtained from TEM observation and 2D WAXD patterns [67] are significant since indicate that the development of the liquid crystal phases did not destroy the self-assembling structures from microphase separation. Thus, both mesogen-jacketed liquid crystalline polymers and polypeptides obtained from controlled polymerization methods are excellent rod-like building blocks to form rod-rod block copolymers with nanoscale hierarchical structures.…”
Section: Supramolecular Organization Of Peptide-synthetic Polymer Hybmentioning
confidence: 71%
See 1 more Smart Citation
“…Both PMPCS and PBLG rods were packed in an interdigitated way in their own domains (Scheme X, d and e). These results obtained from TEM observation and 2D WAXD patterns [67] are significant since indicate that the development of the liquid crystal phases did not destroy the self-assembling structures from microphase separation. Thus, both mesogen-jacketed liquid crystalline polymers and polypeptides obtained from controlled polymerization methods are excellent rod-like building blocks to form rod-rod block copolymers with nanoscale hierarchical structures.…”
Section: Supramolecular Organization Of Peptide-synthetic Polymer Hybmentioning
confidence: 71%
“…Schematic drawings of the shearing geometry with the X-axis being the shear direction are shown in (c) and (e) for lamellar and cylinder structures, respectively. Reprinted with permission from [67]. Copyright (2010) American Chemical Society.…”
Section: Supramolecular Organization Of Peptide-synthetic Polymer Hybmentioning
confidence: 99%
“…Therefore, MJLCP is an excellent rod‐like candidate to build block copolymers with various architectures. Researches on rod‐coil,43 rod–rod,44 triblock,45 and multiarmed46 polymers containing MJLCPs as the rod component have been investigated. However, comb polymers containing MJLCPs as rigid side chains have never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The low intensity and broad shape of the reflections indicate poor molecular packing and hence reduced interaction. So, from the aforesaid data, it is confirmed that compound 4.4 shows columnar nematic phase (N Col ), which is uncommon in the family of discotics.…”
Section: Resultsmentioning
confidence: 69%